Literasi Keuangan pada Anggota Karang Taruna Talang Permai Pematang Gubernur - Rini Indriani Djamaan (TRIBUTE: JOURNAL OF COMMUNITY SERVICES, 2025)
The community service program aims to equip Talang Permai members with the basic skills to budget, save, invest wisely, manage debt healthily, and plan their financial future independently, thereby contributing to improving the quality of their personal and environmental finances in Bengkulu City. The program involves a lecture-based approach, discussions, and workshops, designed to build financial literacy and entrepreneurial skills. The results of the program indicate an increase in participants' understanding of financial management concepts, as reflected in the results of pre- and post-test evaluations. It is recommended that regular mentoring and the involvement of relevant parties, such as academics or local financial institutions, be carried out to expand the material to include simple investment management.